Tryptophan-5-HT pathway disorder was uncovered in the olfactory bulb of a depression mice model by metabolomic analysis - Chen, Guanghui; Zhou, Siqi; Chen, Qiang; Liu, Mengmeng; Dong, Meixue; Hou, Jiabao; Zhou, Benhong (Frontiers in Molecular Neuroscience, 2022)
Major depression (MD) is a severe mental illness and creates a heavy social burden, and the potential molecular mechanisms remain largely unknown. Lots of researches demonstrate that the olfactory bulb is associated with MD. Recently, a gas chromatography-mass spectrometry - based metabolomic studies on depressive rats indicated that metabolisms of purine and lipids were disordered in olfactory bulb. As various physicochemical properties and extensive concentration range, a single analytical technique could not completely cover all metabolites, hence it is necessary to adopt another metabolomic techniques to seek for new biomarkers or molecular mechanisms for depression. Therefore, we adopted a liquid chromatography-mass spectrometry metabonomic technique in chronic mild stress (CMS) model to investigate significant metabolic changes in olfactory bulb of the mice. We discovered and identified 16 differential metabolites in olfactory bulb of the CMS treatments. Metabolic pathway analysis by MetaboAnalyst was generated according to the differential metabolites, which indicated that tryptophan metabolism pathway was the core pathogenesis in the olfactory bulb of CMS depression model. Further, the expressions of tryptophan hydroxylase (TpH) and aromatic amino acid decarboxylase (AAAD) were detected by western blotting and immunofluorescence staining. The expression of TpH was increased after CMS treatment, and the level of AAAD was unaltered. These results revealed that abnormal metabolism of tryptophan pathway in olfactory bulb mediated the occurrence of MD.